Optimalisasi Penggunaan Media ICT dalam Pembelajaran IPA untuk Meningkatkan Hasil Belajar Siswa Kelas IXc Pada Semester II Tahun 2014/2015 di SMPN 4Kota Solok - Hurriyati Hurriyati (Pendidikan Biologi FKIP UMMY, 2019)
This research is motivated by the conditions when learning which seems to tend to make students less motivated to learn science. Students sometimes feel scared, lazy and bored because they think that science is difficult, full of formulas and so many concepts must be memorized that students expect the science class to end soon. On the other hand students will be able to involve themselves fully both emotionally and intellectually when seeing a spectacle on the screen. When the author occasionally utilizes ICT media in student learning seems motivated to follow it. The purpose of this study was to achieve the blessing of Allah SWT by trying to optimally improve the quality of learning through the effort